Peculiarities of the Factorial Structure of the Functional State in Children Aged 9–10 Years - Krivolapchuk, I. A.; Chernova, M. B. (Human physiology, 2019)
The factors that determine the functional state (FS) as an integral characteristic of the total body were identified in children aged 9–10 years ( n = 168) and included the autonomic regulation of physiological functions (factor I), the efficiency of cognitive activity (factor II), physical working capacity (factor III), hemodynamic support of cognitive activity (factor IV), nonspecific resistance of the body (factor V), and overall working capability (factor VI). The factors were considered as separate FS aspects that reflects activities of different functional systems. Using a systemic approach, the physiological contents of the factors were established, the most informative indices were identified for FS evaluation, and reference values were proposed for comparisons and diagnosis of the FS in children of the age group in question in a school setting. Aerobic and anaerobic components of the physical working capacity and motor fitness were shown to correlate with the efficiency of cognitive activity and nonspecific resistance to catarrhal diseases as FS aspects. The factorial structure of the FS in children aged 9–10 years was found to be similar to that in subjects of 5–6 and 13–14 years of age. Based on the finding, the factors were assumed to be the most stable FS components forming during ontogeny.